E-VILLAGE GOVERNMENT: FOR TRANSPARENT AND ACCOUNTABLE VILLAGE GOVERNANCE - Novita Puspasari (Association of Certified Fraud Examiners Indonesia Chapter, 2017)
ABSTRACTE-village government is a breakthrough that can be used by village to support the village governance’s transparency and accountability after the issuance of Village Law. Of the 301 villages in Banyumas, only 47 villages have village website on their own initiative. Of the 47 villages that have website, only 4 villages have informative, timely, relevant, and sufficien website which can be used as a medium for two-way communication between village government and the people. Village location that is close to the district capital and educational level of village people do not make the village more responsive in supporting the development of e-village government. Progressive and innovative village leaders are the main factors in implementing e-villagegovernment. Some villages have not implemented e-village government because they still have lack of human resources, lack of experience and lack of supervision.